Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Pelanggan Melalui Word Of Mouth Pada UMKM Bakso Perintis Bogor - Mohammad Fahrizal; Hadita Hadita; Neng Siti Komariah; Dewi Puspaningtyas Faeni; Yayan Hendayana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine whether the Quality of Service Product Quality on Customer Satisfaction Through Word Of Mouth at UMKM Bakso Perintis Bogor. The method used in this study is a quantitative method. The population in this study were consumers at Bakso Perintis customers who live in Perumahan Pura Bojong Gede, Jalan Boulavard Timur Raya, Tajur Halang District, Tajur Halang Village, Bogor, West Java. The use of samples in this study used a non-probability sampling technique with the calculation of the Lemeshow formula, which obtained 100 consumers. Data analysis using Smart PLS 3.0. The analysis methods used are descriptive analysis, validity test, reliability test, r-square test, q-square test and hypothesis test. The results of the study indicate that: 1). Service quality cannot directly affect word of mouth. 2). Product quality cannot directly affect word of mouth. 3). Service quality can affect customer satisfaction. 4). Product quality can affect customer satisfaction. 5). Word of mouth cannot directly affect customer satisfaction. 6). Word of mouth does not mediate service quality on customer satisfaction. 7). Word of mouth does not mediate product quality on customer satisfaction.